Psychiatry Department Response to the Boston Marathon Bombings Within a Level-1 Trauma Center. Issue 3 (May 2015) - Oser, Megan; Shah, Sejal B.; Gitlin, David
Abstract : Abstract: In this article we present how the consultation-liaison and psychology divisions of an academic medical center's Department of Psychiatry responded in the first week after the Boston Marathon bombings, specifically in the context of disaster response guidelines and evidence-based approaches to acute trauma. Since the department had to address several complicated matters at multiple levels within the hospital system, we highlight unexpected issues unique to this particular event as they arose within the primary domains of our involvement. This article aims to (1) provide a descriptive analysis of how we enacted disaster and trauma guidelines and evidence-based care within a hospital setting, (2) shed light on the unique and unexpected administrative and systemic issues encountered in our response, and (3) discuss lessons learned, including opportunities to improve trauma-related care.